Potential uptake of phosphorus by catch crops in greenhouse conditions and release after freezing-thawing - Khalaf, Rafa Abdulhassan (SLU/Dept. of Soil and Environment, 2013)
Catch crops are an important component of cropping systems in Sweden and other Scandinavian countries, but may contribute to phosphorus (P) losses after freezingthawing cycles (FTCs). Eight existing and new catch crop species in Swedish farming were grown in a greenhouse to study potential P uptake and P release from shoots, roots and whole plants after FTCs. The catch crop species were structurator (Raphanus sativus L. var. longipinnatus), white mustard (Sinapis alba L.), oilseed radish (Raphanus sativus var. oleiferus.), phacelia (Phacelia tanacetifolia L.), red clover (Trifolium pratense L.), chicory (Cichorium intybus L.), perennial ryegrass (Lolium perenne L.) and cocksfoot (Dactylis glomerata L).